Bibliografía española de Derecho penal (octubre de 2003 a marzo de 2004) - Higuera Guimerá, Juan-Felipe; Alastuey Dobón, Carmen; Rueda Martín, Mª. Ángeles; Vizueta Fernández, Jorge; Escuchuri Aisa, Estrella; Mayo Calderón, Ana Belén; Fernández Ibáñez, Eva (Revista de Derecho Penal y Criminología, 2019)
-